Evaluation of n-butanol as an oxygenated additive to improve combustion-emission-performance characteristics of a diesel engine fuelled with a diesel-calophyllum inophyllum biodiesel blend - Imtenan, S.; Masjuki, Haji Hassan; Varman, M.; Fattah, I.M.R. (Royal Society of Chemistry, 2015)
Alexandrian laurel or Calophyllum inophyllum oil is considered as one of the most forthcoming non-edible biodiesel sources in recent years. In the present study, the relative improvement of an Alexandrian laurel biodiesel-diesel blend (AL20) was attempted with the addition of 5-10 n-butanol (by vol), which is often used as an oxygenated cold starting additive. Constant 80 Nm torque at variable engine speed, ranging from 1000 to 3000 rpm was chosen as the operating condition on a 4-cylinder turbocharged, water cooled diesel engine. Brake specific fuel consumption (BSFC), brake specific energy consumption (BSEC) and brake thermal efficiency (BTE) was measured to compare the performance of the test fuels quantitatively. Engine emissions such as unburned hydrocarbons (HC), carbon monoxide (CO), nitrogen oxide (NO) and smoke opacity were also measured. Alcoholic oxygenated additives like n-butanol generally reduces the in-cylinder temperature. Therefore, in-cylinder pressures of the test fuels were acquired and the heat release rates (HRR) were analyzed to unveil the characteristics of the combustion mechanism. Correlation of performance and emission was made to the combustion parameters to obtain a better understanding of the scenario. However, in a nut-shell, the investigation exposes the potential of n-butanol to be used as the modifier of the AL biodiesel-diesel blend in the context of combustion, performance and emission characteristics.